1993
DOI: 10.1159/000119026
|View full text |Cite
|
Sign up to set email alerts
|

Single Doses of Piracetam Affect 42-Channel Event-Related Potential Microstate Maps in a Cognitive Paradigm

Abstract: We examined whether a single administration of piracetam produces dose-dependent effects on brain functions in healthy young men. In 6 subjects, 42-channel event-related EEG potential maps (ERP) were recorded during a task requiring subjects to watch single digits presented in a pseudorandom order on a screen and to press a button after all triplets of three consecutive odd or even digits. The ERP maps to the three digits of the correctly detected triplets were analyzed in terms of their mapped ERP field confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In the present analysis, the map topographies were assessed by a feature extraction that resulted in the centroid descriptors. It has been shown that the latencies of the microstates are closely similar if the maps are compared directly by correlating their voltage distributions (full topographic information applying Global Map Dissimilarity) instead of the extracted spatial features and even if the latencies of the distribution-independent Global Field Power minima are used as in Michel and Lehmann (1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, the map topographies were assessed by a feature extraction that resulted in the centroid descriptors. It has been shown that the latencies of the microstates are closely similar if the maps are compared directly by correlating their voltage distributions (full topographic information applying Global Map Dissimilarity) instead of the extracted spatial features and even if the latencies of the distribution-independent Global Field Power minima are used as in Michel and Lehmann (1993).…”
Section: Discussionmentioning
confidence: 99%
“…They observed single digits appearing on a screen in a pseudo-random order, and they were requested to press a microswitch whenever the last three digits were either odd or even ("triplets"; Michel and Lehmann, 1993). The single digits subtended 1.5 degrees visual angle, and were presented at intervals of 704ms; each was shown for 100ms duration.…”
Section: Methodsmentioning
confidence: 99%
“…Only those stimuli were used which are expected to elicit similar and relatively simple cognitive processing without specific anticipations such as represented by the contingent negative variation (McCallum, 1988) and without responses to occurrences or nonoccurrences of expected targets ("update", "closure", "mismatch"; Kutas and Hillyard, 1980;Picton, 1992;Michel and Lehmann, 1993). Within the series of the presented odd (O) or even (E) digit stimuli, a new stimulus may (1) follow an O-E-or E-O-sequence.…”
Section: Analyzed Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of ERPs was performed by microstate analysis. This analysis is based on the observation that the brain electrical field (EF) on the scalp (map) stays nearly stable over a time segment (microstate) followed by a sudden change of EF characterizing the next microstate [Michel and Lehmann, 1993;Pascual-Marqui et al, 1995b]. Different landscapes of the maps indicate different configurations of the activated neural population and therefore partially reflect different functional microstates of the brain [Brandeis and Lehmann, 1989;Michel and Lehmann, 1993].…”
Section: Introductionmentioning
confidence: 99%